Research on Efficient Soft Switching Based on MPPT of PV Power Generation System - Tao, Peng; Cui, Yan; Liang, Jiayuan (Frontiers in Energy Research, 2021)
In this paper, the basic soft switching technology is proposed based on hard switching, and then the basic soft switching technology is optimized and an improved soft switching technology is proposed to improve the conversion efficiency by reducing the switching loss. The simulation results show that the conversion efficiency of hard switching and basic soft switching is 94.3% and 96.1%, but the conversion efficiency of improved soft switching optimized on the basis of basic soft switching is only 95.8%. In order to solve this problem, an innovative soft switching technology is put forward in this paper, and its conversion efficiency is as high as 96.3%, which is superior to the basic soft switching technology.